Depression and Anxiety among Parkinson’s Disease Patients: Prevalence, Risk Factors, and Impact on Life Quality - Shakil Asif, Rizwan Farooq, Unaiza Jawad, Muhammad Shoaib Irfan, Muazzam Fuaad, Subhan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Parkinson’s disease’s common symptoms are anxiety and depression and play a determinant role in the quality of a patient’s life. Numerous studies identified several risk factors but very few investigated the specific risk factors associated with Parkinson’s disease (PD). The objective of the present study was to assess the depression and anxiety among Parkinson’s disease patients, prevalence, risk factors, and impact on life’s quality. Methodology: This cross-sectional study was conducted on 78 Parkinson’s disease patients at the department of Psychiatry & Behavioral Sciences LGH Lahore, Pakistan and Div HQ hospital, Mirpur AJK in collaboration with Neurology department for the duration from 15 May 2021 to 15 November 2021. All the patients were assessed for anxiety and depression. Unified Parkinson’s Disease Rating Scale (UPDRS) and Holmes and Rahe scale were used for the evaluation of staging and severity among Parkinson’s disease patients. Clinically diagnosed Parkinson’s disease patients aged between 25 and 85 years and stages 1 to 4 on the H-Y scale were enrolled. Patients with movement disorders other than PD, atypical Parkinson’s, deep brain stimulation (DBS), visual loss, and secondary Parkinsonism were excluded. Ethical approval was taken from the institutional ethical committee. Depression and anxiety impact on life quality were assessed using World Health Organization Quality of Life (WHOQOL)-BREF. Results: Of the total 78 Parkinson’s disease patients, the prevalence of depression and anxiety was 26 (33.3%) and 32 (41.03%) respectively. About 40 were male and 38 were female patients. The overall mean age was 67±5.9 years. The young population was more susceptible to anxiety and depression was significantly higher in females. The depression and anxiety overlap were in 19 (24.4%) patients. The UPDRS and H-Y scale variance accounted for depression 34.5% and anxiety 38.9%. The severity and advanced disease stage were depression independent predictors whereas younger age and severity were anxiety main predictors. Overall, anxiety and depression had adverse impacts on life quality of Parkinson’s disease patients. Conclusion: Depression and anxiety were found in 33.3% and 41.03% of current Parkinson’s disease patients, respectively. Depression and anxiety are relatively common in Parkinson’s disease. The main risk factors for developing depression were female gender, low socioeconomic status, and a history of depression. Anxiety was associated with a young age and a history of anxiety. Both had a negative effect on one’s quality of life.